Vedic world view & modern science - National Seminar on Vedic World View and Modern Science (2000: Dept. of Sanskrit, Dr. H. S. Gour University); Tripathi, Radhavallabh; Doctor Harisingh Gour Vishvavidyalaya. Sanskrit Department (Delhi : Pratibha Prakashan, 2006)
Contributed papers presented seminar organised under DRS-SAP UGC Program in the Dept. of Sanskrit, Dr. H. S. GourUniversity, Sagar on Oct 17 - 18, 2000
Includes bibliographical references and index
Includes passages in Sanskrit
Keywords: Vedic literature -- History and criticism -- Congresses; Vedas and science -- Congresses